Determination of the Detonation Pressure From a Water Test - Trzciński, W. A.; Cudziło, S.; Szymańczyk, L. (Engineering Transactions, 2015)
In the paper, a semi-empirical method of determining the detonation pressure of high explosives from the so-called water test is proposed. X-ray photographs of expansion of a water envelope being accelerated by the detonation products of a cylindrical charge and results of numerical modelling of the process of water expansion are the basis of the method. The pressure is estimated by comparison of the calculated and recorded profiles of an oblique shock wave propagating in water. The method is applied to determine the detonation pressure for selected high explosives used for military purposes. The results obtained are compared with the experimental values of pressure given in the literature and with the pressures obtained from thermochemical calculations. The estimated detonation pressures differ by less than 5% from those given in literature. It is proved that the accuracy of estimation of the detonation pressure depends generally on the measurement precision of the position of the shock wave front in water. A simplified variant of the method is also proposed in which the numerical modelling of the detonation in water is not needed.